Analysis of the Effect of Customer Experience, with Customer Satisfaction as a Mediation Variable - Andi Juanna; Umin Kango; Tineke wolok; Irwan Yantu; Rober R. Winerungan (Research Parks Publishers, 2022)
The Purpose of this study is to analyze the effect of Customer Experience, Service with Customer Satisfaction as mediation Variable for IndiHome's Customers of PT Telkom Witel Sulut. The population of this research totally 2509 Customer with 2 months unpaid billing of IndiHome on term July and August 2021, and sampling was carried out based on Slovin's Formula total 359 respondents filled the questionnaire. The Research data were analyzed using PLS SEM (Partial Least Square - Structural Equation Modeling) with SmartPLS 3.0.software. The Result show that Customer Experience, on Customer Satisfaction but did not directly influence Customer Retention. Customer Experience, Service Quality and Price Perception affect Customer Retention through Customer Satisfaction with full mediation.